Characterizing the interfacial fracture toughness for microelectronic packaging - Chen, W. T. (2012)
In a microelectronic package there are many interfaces where the adhesion between different materials plays an important role in its reliability issue. Take an example in a flipchip package: delamination at the interfaces between underfill/passivation, underfill/substrate, etc. will lead to the speeded breakdown of the interconnection. Proper characterization of interfacial adhesion strength is very important for process control as well as reliability prediction.